Coaching as a role in the psychologist’s professional activity - Solf Zárate, Arturo (2022)
The present work proposes that one of the roles of the professional psychologist is the work of Coaching, understanding this as the support to the client (coachee) so that he achieves his significant goals. The existence of a new subspecialty in Psychology, Coaching Psychology, which would allow psychologists to carry out Coaching activities with a scientific basis, stands out. In addition, organizational psy xpertise in the application of Solution-Focused Coaching.